Studi Literatur Uji Aktivitas Ekstrak Etanol Daun Anting-Anting (Acalypha indica Linn.) Terhadap Penyembuhan Luka Bakar Pada Hewan Coba - Devilia Rambu Athandau; Meity M Laut; Tri Utami (Jurnal Veteriner Nusantara, 2023)
Burns are injuries that occur due to the body surface touching objects that produce heat, namely heat, radiation, electricity, and/or chemical either direct or indirect contact and resulting in skin damage or tissue loss. Treatment of burns can use chemical compounds or natural compounds from plants.Earring plant is one of the medicinal plants that can be used to heal burns. This literature study aims to determine the compounds contained in earring leaves and their mechanism of action in the process of healing burns. This literature study was conducted through searching and collecting literature using Google Schoolar and then analyzed descriptively. The literature used is 34 literatures that meet the criteria related to research topics with 29.41% discussing earring leaves, 29.41% discussing the pharmacological activity of secondary metabolites and 41.17% discussing wound healing. From the literature study, it is known that earring leaves contain aleurone compounds, flavonoids, alkaloids, saponins, steroids, triterpenoids, terpenoids, tannins, quinones, phenols and glycosides. These secondary metabolites have anti-inflammatory, antibacterial activity, stimulate the formation of new cells and stimulate the growth of collagen, antimicrobials and antioxidants, thereby accelerating burn healing. Wound healing is influenced by flavonoid compounds, alkaloids, saponins, tannins and phenols and affects the stages of inflammation, proliferation and maturation. To support these results, it is necessary to do laboratory research to prove it.